1990
DOI: 10.1136/bjo.74.12.731
|View full text |Cite
|
Sign up to set email alerts
|

Objective autorefraction in posterior chamber pseudophakia.

Abstract: Automated refraction with the Canon RK-1 Autoref keratometer was evaluated in 110 eyes (110 patients) six to eight weeks after they had undergone extracapsular cataract extraction with posterior chamber intraocular lens implantation and achieved a best corrected visual acuity of at least 6/12. Autorefraction readings were obtained in 100 (91%) of these eyes. The agreement between autorefraction and clinical refraction data was 98% for spherical equivalence less than 0.51 dioptres (D), 95% for sphere power less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Previous studies also showed that autorefractor measurements were not significantly different from subjective refraction. [24][25][26] A fourth limitation is that corneal astigmatism was measured from the anterior corneal surface. Previous studies showed that ignoring posterior corneal astigmatism results in errors in the estimation of total corneal astigmatism.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also showed that autorefractor measurements were not significantly different from subjective refraction. [24][25][26] A fourth limitation is that corneal astigmatism was measured from the anterior corneal surface. Previous studies showed that ignoring posterior corneal astigmatism results in errors in the estimation of total corneal astigmatism.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the accuracy of AR decreases in other clinical situations (eg, media opacities, previous corneal refractive surgery). 22,23,[30][31][32][33] We evaluated the repeatability of AR in eyes with the ReZoom IOL and found that the first AR measurement and the means of the 3 AR measurements for nondilated pupils and dilated pupils were not significantly different. We also found that multiple measurements did not improve the agreement between AR measurements and MR measurements.…”
Section: Discussionmentioning
confidence: 99%
“…However, the reliability of AR decreases in some circumstances, such as in eyes with media opacities and IOLs, due to the scattering of the infrared beam used by these instruments. [20][21][22][23] The current study was designed to compare the repeatability and accuracy of MR and AR in patients with ReZoom IOLs. To our knowledge, there are no previous studies of the validity of AR after ReZoom multifocal IOL implantation.…”
mentioning
confidence: 99%
“…Automated refraction (AR) after cataract surgery with monofocal IOLs is considered a proper starting point for subjective manifest refraction 3,4 . It has been shown that with bifocal diffractive IOL, there is a good correlation between AR and subjective refraction 5 , while with bifocal refractive IOLs, there was a lesser correlation between those parameters.…”
Section: Introductionmentioning
confidence: 99%